The Kandungan Fitokimia dan Aktivitas Antioksidan Krim Fraksi Etanol Kulit Buah Jeruk Manis (Citrus sinensis (L.) Osbeck) - WAHYUNITA YULIA SARI; Definingsih Yuliastuti; Maria Ulfa (Fakultas Farmasi Universitas Setia Budi, 2022)
Sweet citrus fruit is generally used on the pulp, while the peel only becomes waste. Waste of sweet orange fruit peel is often found in the community which contains antioxidant compounds. Waste of sweet orange fruit peel can be processed into cream preparations that can be used by the community. Cream from waste of sweet orange fruit peel is made using maceration extraction and liquid-liquid fractionation methods. The maceration extraction method used 70% ethanol as solvent, while the fractionation method used n-hexane, ethyl acetate and 70% ethanol as solvents. Cream of 70% ethanol fraction of sweet orange fruit peel is made in several formulas of FI (3%), FII (6%) and FIII (9%). Screening for the phytochemical content of sweet orange fruit peels was carried out using chemical reagents. Sweet orange fruit peel contains vitamin C compounds, flavonoids and essential oils. Cream preparations with 70% ethanol fraction of orange fruit peels (FI, FII, FIII) indicate that the cream has good color, texture and physical properties.